Pattern of Nosocomial Infections in Neonatal Intensive Care Unit - Aqib, Aqib Rashid; Shah, Marij Ullah; Shah, Syed Awais ul Hassan; Ali, Faryal; Usman, Ayesha; Iqbal, Aamir (Indus Journal of Bioscience Research, 2025)
Background and Aim: Hospital-acquired infections continue to be a major contributor to morbidity and mortality in neonates, especially in neonatal intensive care units (NICUs). Timely recognition of causative organisms ensures appropriate treatment as well as infection control. Therefore, the objective of this study was to evaluate the pattern of nosocomial infections in the neonatal intensive care unit (NICU) of Combined Military Hospital (CMH) Peshawar. Patients and Methods: A cross-sectional study conducted on 177 neonates (aged 3 to 28 days) in the Department of Pediatric Medicine, CMH Peshawar from April 2024 to November 2024. All the neonates admitted for >48 hours and fulfilling operational criteria for nosocomial infection, were enrolled. Data collection included demographic and clinical details, physical examination, and laboratory investigations (CBC, CRP, blood/urine cultures, chest X-ray). Organisms identified through standard culture methods. Data analysis was performed using SPSS v23, with qualitative and quantitative variables summarized using frequencies, percentages, means, or medians as appropriate. Chi-square test applied for stratified data with a significance level of p ≤ 0.05. Results: Out of 177 neonates, there were 103 (58.2%) male and 74 (41.8%) female. Hyaline membrane disease was the leading cause found in 90 (50.8%) neonates followed by transient tachypnea of the newborn 14 (7.9%), meconium aspiration syndrome 11 (6.2%), and birth asphyxia 7 (4%). Approximately, 24 (13.6%) neonates had congenital anomalies. The overall mean of hospitalization was 13.8 ±16.5 days. Regarding mode of delivery, the frequency of unassisted vaginal delivery, cesarean section, and instrumental delivery was 89 (50.3%), 84 (47.5%), and 4 (2.3%), respectively. Among 177 neonates, nosocomial infections (NIs) developed in 36 (20.3%) and incidence rate of approximately 14.5 infections per 1000 patient-days. Based on infection’s sites, the lungs (pneumonia) were affected in 88 (49.7%) neonates followed by bloodstream infections 74 (41.8%), skin and soft tissue infections 11 (6.2%), and urinary tract infections 4 (2.3%). Staphylococcus species (23.5%), Klebsiella species (22%), and Enterobacter cloacae (20.6%) were the most commonly isolated pathogens from clinical specimens. Conclusion: Organisms such as Staphylococcus species and Klebsiella species mostly cause the nosocomial infections among neonates. To reduce the hospital-acquired infections in NICU, the early diagnosis, continuous surveillance, and targeted antimicrobial therapy are essential.